Factors Affecting the Prescription Pattern of Generic Cardiovascular Medicines: A Cross-Sectional Study in Dhaka City (Dhaka University Journal of Pharmaceutical Sciences, 2022)
A growing trend of cardiovascular disease is a threat to national health. The objectives of the research are to analyze the association between prescribed generics with doctors’ gender, academic degrees, location of practice and categories of generic medicines. A descriptive cross-sectional Dhaka-based study design was used to assess the prescriptions data. As a primary source of data, 403 prescriptions were collected for twelve months from six different locations of the cardiologists’ practice chamber in Dhaka. A two-stage cluster sampling technique was used to collect prescriptions at a 95% confidence level with a 5% margin of error. For proportional to population size (PPS) sampling, cluster weight of specific areas was determined from a secondary source of data. Chi-Square (2) goodness fit test revealed that gender, academic degrees, location of practice, therapeutic class of cardiovascular generics are statistically significant in association with prescribed generic medicine at a 5% level of significance (pvalues